Joint digitization of heterogeneous university collections using semantic web technologies - Wagner, Sarah; Görz, Günther; Fichtner, Mark; Andraschke, Udo (CEUR Workshop Proceedings, 2019)
In a collaborative effort between IT and museum experts, the research project “Objekte im Netz” aims at developing a joint digitization strategy for the digital documentation of heterogeneous university collections by applying semantic web technologies. The University of Erlangen-Nuremberg owns more than 20 different scientific collections. So far, each collection has documented and stored its object data in different ways, thus making it impossible to interlink the information. The data has neither been stored in a sustainable way nor has it been reusable. In summary, the stored information is not utilized to its full potential. This is a typical scenario regarding scientific collections at universities in German-speaking countries. In order to allow consistent documentation for all collections, a data model based on ICOM’s CIDOC Conceptual Reference Model is currently in development. The model uses sample data of six representative collections of the University of Erlangen-Nuremberg. In the future, this model should serve as a best practice for other university collections. This approach ensures homogenous documentation as well as long-term interpretability, and offers an opportunity to participating collections to aggregate the cross-collection information in a portal, allowing research on the objects as well as their presentation. This paper outlines the current state of the data model, the resulting application ontology, and their integration into the virtual research environment “WissKI”.
CRIS-Team Scopus Importer:2019-06-21